Baseline frontostriatal‐limbic connectivity predicts reward‐based memory formation - Hamann, Janne M. (Hum Brain Mapp, 2014)
Reward mediates the acquisition and long‐term retention of procedural skills in humans. Yet, learning under rewarded conditions is highly variable across individuals and the mechanisms that determine interindividual variability in rewarded learning are not known. We postulated that baseline functional connectivity in a large‐scale frontostriatal‐limbic network could predict subsequent interindividual variability in rewarded learning. Resting‐state functional MRI was acquired in two groups of subjects (n = 30) who then trained on a visuomotor procedural learning task with or without reward feedback. We then tested whether baseline functional connectivity within the frontostriatal‐limbic network predicted memory strength measured immediately, 24 h and 1 month after training in both groups. We found that connectivity in the frontostriatal‐limbic network predicted interindividual variability in the rewarded but not in the unrewarded learning group. Prediction was strongest for long‐term memory. Similar links between connectivity and reward‐based memory were absent in two control networks, a fronto‐parieto‐temporal language network and the dorsal attention network. The results indicate that baseline functional connectivity within the frontostriatal‐limbic network successfully predicts long‐term retention of rewarded learning. Hum Brain Mapp 35:5921–5931, 2014. © 2014 Wiley Periodicals, Inc.